1998
DOI: 10.1080/09540129850124433
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and burnout among buddies: Demographic, situational and motivational factors

Abstract: Work-related psychological distress (burnout) is a probable cause of drop-out among emotional support volunteers (buddies) who work with people living with AIDS. In addition to the emotional suffering and disruption to both the buddy and the buddied, burnout has significant cost implications for voluntary organizations in terms of training and recruitment. The aim of this study was to identify the demographic, situational and motivational factors associated with burnout among buddies with the intention of iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
3
26
1
Order By: Relevance
“…This has been reported in research investigating burnout among peers (Maslanka, 1996;Claxton et al, 1998;Christensen et al, 1999). Maslanka (1996) reported that burnout arose from the stress of working with a high-demand population, emotional exhaustion, and lack of personal accomplishment.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This has been reported in research investigating burnout among peers (Maslanka, 1996;Claxton et al, 1998;Christensen et al, 1999). Maslanka (1996) reported that burnout arose from the stress of working with a high-demand population, emotional exhaustion, and lack of personal accomplishment.…”
Section: Discussionmentioning
confidence: 81%
“…Most peer support research in the area of HIV has been limited to HIVnegative volunteers who have provided social support to HIV-positive individuals. Notably, the majority of HIV social support interventions have utilized volunteers who are white heterosexual women or gay men (Christensen et al, 1999;Maslanka, 1996;Claxton et al, 1998;Cassel & Ouellette, 1995). No studies we could locate have examined the psychological benefits for an HIV-positive peer providing the support.…”
mentioning
confidence: 99%
“…The volunteer process has been examined in terms of a small group of phenomena, most notably motives or functions (Omoto and Snyder 1995;Penner 2002), individual differences (Okun et al 2000) and role identity (Grube and Piliavin 2000). These concepts have been largely explored through cross-sectional and short-term longitudinal research designs (Claxton et al 1998;Kiviniemi et al 2002).…”
Section: Research Issuesmentioning
confidence: 99%
“…The current study is situated within the context of HIV=AIDS volunteering due to the prominence of burnout problems among these volunteers. For example, Claxton, Catalan, and Burgess (1998) found that 75% of HIV=AIDS volunteers reported moderate or high levels of burnout. Burnout within HIV=AIDS volunteers has been associated with mental health problems.…”
mentioning
confidence: 96%